A novel type of silencing factor, Clr2, is necessary for transcriptional silencing at various chromosomal locations in the fission yeast Schizosaccharomyces pombe - Bjerling, Pernilla (Oxford University Press, 2004)
The mating-type region of the fission yeast Schizosaccharomyces pombe comprises three loci: mat1, mat2-P and mat3-M. mat1 is expressed and determines the mating type of the cell. mat2-P and mat3-M are two storage cassettes located in a 17 kb heterochromatic region with features identical to those of mammalian heterochromatin. Mutations in the swi6(+), clr1(+), clr2(+), clr3(+), clr4(+) and clr6(+) genes were obtained in screens for factors necessary for silencing the mat2-P–mat3-M region. swi6(+) encodes a chromodomain protein, clr3(+) and clr6(+) histone deacetylases, and clr4(+) a histone methyltransferase. Here, we describe the cloning and characterization of clr2(+). The clr2(+) gene encodes a 62 kDa protein with no obvious sequence homologs. Deletion of clr2(+) not only affects transcriptional repression in the mating-type region, but also centromeric silencing and silencing of a PolII-transcribed gene inserted in the rDNA repeats. Using chromatin immunoprecipitation, we show that Clr2 is necessary for histone hypoacetylation in the mating-type region, suggesting that Clr2 acts upstream of histone deacetylases to promote transcriptional silencing.